Neogene to quaternary foraminifera from the western margin of southern Africa - Bergh, Eugene (Department of Geological Sciences, 2019)
The western margin of southern Africa underwent major palaeoceanographic changes since the initiation of the Benguela Upwelling System during the Neogene. Microfossils in marine sediments provide key proxies in our understanding of how the margin evolved. Fossil shells (tests) of foraminifera (singlecelled protists) from twenty cores from the Namibian shelf (199 to 309 m water depth) and three cores from the western slope (874 to 3631 m water depth) of South Africa were studied to determine the middle Miocene to Quaternary stratigraphy, palaeoenvironment and palaeoceanography of the western margin of southern Africa. Cores from the Namibian shelf recovered middle Miocene calcareous mud in erosional contact with overlying Pliocene to Pleistocene phosphatic sediments. Strontium isotope stratigraphy and planktic foraminifera biostratigraphy provide age control of the Namibian shelf sediments. The planktic indicator species Globoquadrina dehsicens and Globigerinoides bisphericus support strontium isotope stratigraphy results for the olive-green mud unit of the northern Namibian shelf indicating an age of 16 to 14 Ma, and the overlying Plio-Pleistocene age of the phosphorite-rich unit supported by planktic indicator species Globorotalia truncatulinoides and Globorotalia (Globoconella) inflata. Middle Miocene foraminifera reflect a warmer, oligotrophic, subtropical, deeper environmental setting in contrast to the shallower depositional environment, cooler conditions and a eutrophic bottom water setting indicated by Pleistocene foraminifera in the phosphatic units. The palaeoenvironment on the Namibian shelf was progressively shoaling during the Pleistocene as sea level amplitudes increased. An Uvigerina spp.- dominated association occurs in deeper shelf deposits dated to the early Pleistocene and the Ammonia beccarii association occurs in shallower shelf deposits of the late Pleistocene to Holocene. The planktic and benthic foraminiferal stable oxygen isotope records, colour reflectance (L*) and non-carbonate mineral counts provide age control on cores from the western slope of South Africa, whose records extend to just beyond Glacial Termination (GT) II. Sediment and benthic foraminiferal accumulation rates were higher during interglacial periods and lower during glacial periods. The major planktic species in the slope cores include Globorotalia (Globoconella) inflata, Globigerina bulloides and Neogloboquadrina incompta. Principal component analysis (PCA) reveals that the major factors influencing planktic foraminiferal abundances are upwelling intensity, the penetration of colder waters during glacial periods and the inflow of subtropical waters from the South Indian Ocean during interglacial periods. The major benthic species in the slope cores include Uvigerina peregrina, Uvigerina hispidocostata and Cibicidoides wuellerstorfi indicating the delivery of organic matter and oxygen availability to have the largest influence on the benthic foraminiferal faunal composition. Uvigerina spp. on the slope show increased relative abundances during periods of lower oxygen conditions. Bottom water masses identified by Nd (neodymium isotopic compositions) values recorded by foraminifera, along with the stable carbon isotope composition and abundance of the benthic foraminifer C. wuellerstorfi indicate shifts from Southern Component Water to North Atlantic Deep Water during GT II and I. Variation in Nd values in an upper slope core (874 m water depth) indicate Antarctic Intermediate Water (AAIW) influence was stronger during glacial periods compared to interglacial periods.